(untitled) (Research, Society and Development, 2021)
The adequacy of the best storage temperature for fruits and vegetables is an essential measure that helps in maintaining quality and extending shelf life. In this sense, this work aimed to study the influence of temperature on the quality of the marolo (Annona crassiflora Mart) “in natura”, where the fruits were washed, sanitized with 1,216 µM hypochlorite solution, and stored at 4 different temperatures (0, 6, 12, and 20 ° C) controlling the relative humidity (80 to 90%). The parameters color L*a*b*, pH, titratable acidity, soluble solids, firmness, total and soluble pectins, enzymes (pectinamethylesterase and polygalacturonase), and vitamin C were analyzed at different storage times. The maximum storage period was 8 days for fruits kept at 0 and 6 °C. The use of higher temperatures (12 and 20 °C) resulted in a shorter storage time (6 and 4 days, respectively). We found that the color parameter L*a*b* was not influenced by time and temperature during the process, while firmness and soluble solids were affected only by temperature. On the other hand, the parameters pH, titratable acidity, total and soluble pectin, enzymes (pectinamethylesterase and polygalacturonase), and vitamin C were influenced by both temperature and storage time (p <0.05). Thus, we prove that to increase shelf life and maintain the best characteristics for consumption, the marolo must be stored between 0 and 6 °C.